Underwater stabilizer for offshore wind power grouting material and preparation method of underwater stabilizer

By using homemade monomer and polymer technology, high-performance offshore wind power grouting underwater stabilizer is prepared, which solves the problems of poor performance of existing products and complex preparation processes, and achieves the effect of improving the stability and durability of offshore wind power grouting materials.

CN119591784AActive Publication Date: 2025-03-11SHANDONG JIANZHU UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510140123.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-08
Publication Date
2025-03-11
Estimated Expiration
2045-02-08

AI Technical Summary

Technical Problem

There are fewer types of underwater stabilizer products for offshore wind power grouting, imperfect performance, poor compatibility, and complex preparation process, long time and high cost, making it difficult to meet the application needs of offshore wind power grouting.

Method used

The low-molecular-weight polyacrylamide offshore wind grouting underwater stabilizer is prepared by using homemade monomers such as sodium acrylate, acrylamide, 2-acrylamide-2-methylpropanesulfonic acid, combined with a redox system, a crosslinking agent and a molecular weight limiting agent, and a low-molecular-weight polyacrylamide offshore wind grouting material is prepared through aqueous solution polymerization and supergravity synthesis technology.

Benefits of technology

It improves the stability and water retention of the cement-based cementitious material system, enhances the stability of underwater construction of offshore wind power grouting materials, reduces strength losses, improves overall stability and durability, solves problems such as water leakage, separation and erosion, and has a simple preparation process and low production cost, which is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119591784A_ABST
    Figure CN119591784A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of building materials, and relates to an underwater stabilizer for an offshore wind power grouting material and a preparation method of the underwater stabilizer, and the underwater stabilizer comprises the following components in parts by weight: 3.1-3.8 parts of self-made monomer sodium acrylate; 10.0 to 10.5 parts of acrylamide; and 10.0 to 10.5 parts of 2-acrylamide-2-methylpropanesulfonic acid (2-acrylamide-2- 0.060 to 0.065 part of a cross-linking agent; 0.40 to 0.45 part of a molecular weight limiting agent; 2.0 to 2.5 parts of a free radical oxidant; 1.0-1.2 parts of a free radical reducing agent; 250 to 370 parts of deionized water; and 0.2-0.3 part of a low-temperature synthetic small material. The underwater stabilizer for the offshore wind power grouting material is uniform in molecular weight distribution, stable in product performance and good in compatibility with a polycarboxylic acid water reducing agent, the stability and the water-retaining property of a cement-based cementing material system are effectively improved, the underwater construction stability of the offshore wind power grouting material is enhanced, and the strength loss is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of building materials and relates to an underwater stabilizer for offshore wind power grouting material and a preparation method thereof. Background Art

[0002] Offshore wind power refers to wind power generation projects built on the ocean. As an important part of the development of clean energy, offshore wind power has attracted much attention. Grouting materials are needed in the foundation structure of offshore wind power to fix the foundation of the wind turbine generator set to provide stable support and ensure the safe operation of the project.

[0003] Factors such as salt and humid climate in the marine environment place high demands on the durability and stability of grouting materials. At the same time, the construction environment of offshore wind power projects is complex and offshore construction is difficult. Underwater stabilizers for offshore wind power grouting materials can improve the stability and water retention of cement-based cementitious materials systems. Especially when medium and low strength offshore wind power grouting materials are mixed with a large amount of high-efficiency water reducer, underwater stabilizers for offshore wind power grouting materials are often required to improve the cohesiveness of the offshore wind power grouting material mixture to ensure that the workability and pumpability of the newly mixed offshore wind power grouting materials can meet the construction requirements.

[0004] At present, there are few types of underwater stabilizers for offshore wind power grouting materials studied at home and abroad, and their performance is not perfect. They have poor compatibility with mainstream polycarboxylic acid-based water reducers and cannot meet the application needs of various types of offshore wind power grouting materials. At the same time, the preparation process of most underwater stabilizers for offshore wind power grouting materials is relatively complicated, the synthesis time is long, and the production cost is high, which is not conducive to large-scale production. Therefore, it is urgent to develop a method that can increase the underwater stabilizer of wind power grouting materials to ensure construction efficiency and quality. Summary of the invention

[0005] In view of the deficiencies of the above-mentioned prior art, the present invention provides an underwater stabilizer for offshore wind power grouting material and a preparation method thereof. The specific technical scheme is as follows: The first object of the present invention is to provide an underwater stabilizer for offshore wind power grouting material, comprising the following components in parts by weight: Homemade monomer sodium acrylate (SA) 3.1-3.8 parts; acrylamide (AM) 10.0-10.5 parts; 2-acrylamide-2-methylpropanesulfonic acid (AMPS) 10.0-10.5 parts; cross-linking agent 0.060-0.065 parts; molecular weight limiter 0.40-0.45 parts; free radical oxidant 2.0-2.5 parts; free radical reductant 1.0-1.2 parts; deionized water 250-370 parts; low-temperature synthetic small material 0.2-0.3 parts; The self-made monomer sodium acrylate (SA) is prepared by neutralizing acrylic acid (AA) with sodium hydroxide; The low-temperature synthetic small material is an alkali metal phosphate with reducing properties; the molecular weight limiting agent is sodium methyl methacrylate sulfonate (SMAS).

[0006] The present invention is based on the principle of free radical polymerization and starts from the perspective of molecular structure design. Sodium acrylate (SA), acrylamide (AM) and 2-acrylamido-2-methylpropanesulfonic acid (AMPS) are used as main polymerization monomers, functional groups such as sodium carboxylate group, amide group and sulfonic acid group are introduced, and molecular weight limiter, cross-linking agent and redox system composed of free radical oxidant and free radical reductant are added to design the polymer molecular structure.

[0007] Among them, the raw materials of homemade monomer sodium acrylate (SA) are easy to obtain and the synthesis is simple. The sodium carboxylate group (-COONa) can not only ionize the carboxylate anion group (-COO-) with negative charge in the solution system, but also combine with the heterogeneous charges on the surface of cement particles under the action of electrostatic force to improve the adsorption capacity of polymer molecules. At the same time, it can also improve the hydrophilicity of polymer molecules, which can effectively improve the adsorption and water solubility of polymer molecules, thereby improving the dispersion ability of underwater stabilizers and making underwater stabilizer products more compatible with mainstream polycarboxylate water reducers; the amide group (-CONH2) is a hydrophilic group, which can fix the free water in the system by adsorbing water molecules, thereby playing a role. It has a certain water-retaining and thickening effect; the sulfonic acid group (-SO3H), like the sodium carboxylate group, can be adsorbed on the surface of cement particles through electrostatic force and provide a certain dispersibility. At the same time, the presence of a conjugated dp large π bond in the sulfonic acid group makes it insensitive to the attack of acid, alkali and salt ions, thereby giving the polymer molecule a certain anti-sensitivity; at the same time, by adding low-temperature synthetic small materials, the reaction activation energy of the polymerization system can be greatly reduced, so that the polymerization reaction can be carried out at room temperature or even at low temperature without heating; by adding a molecular weight limiter and reasonably controlling the dosage, the main chain length of the polymer molecule can be adjusted, thereby controlling the relative molecular mass of the polymer, and effectively avoiding the occurrence of the "explosion" phenomenon.

[0008] Furthermore, the method for preparing the homemade monomer sodium acrylate (SA) comprises the following steps: (a) adding 30-50 parts by weight of deionized water and 1.0-1.5 parts by weight of acrylic acid to a reaction kettle, and starting stirring; (b) Sodium hydroxide was added to the reaction kettle to adjust the pH value of the solution to 7-8, and nitrogen was immediately introduced into the reaction kettle to react for 15-25 minutes to generate the homemade monomer sodium acrylate.

[0009] Furthermore, the cross-linking agent is one or more of N,N-methylenebisacrylamide (MBA), carbodiimide, and 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane cross-linking agent.

[0010] The cross-linking agent used in the present invention has two unsaturated double bonds in its molecular structure, so other groups or molecular chains can be grafted at both ends of the molecule. By reasonably controlling the amount of the cross-linking agent, not only the relative molecular mass of the polymer can be significantly increased, but also the molecular structure of the polymer can form a cross-linked network structure, thereby preventing the migration of free water in the offshore wind power grouting material system, and effectively improving the cohesiveness and water retention of the offshore wind power grouting material system.

[0011] Furthermore, the free radical oxidant and the free radical reductant constitute a redox system, and the redox system is a tert-butyl peroxide (TBHP)-sodium bisulphite formaldehyde (SFS) redox system, a diacyl peroxide-cyclohexane salt system or a dialkyl peroxide-thiol system; the tert-butyl peroxide (TBHP)-sodium bisulphite formaldehyde (SFS) system is that the free radical oxidant is tert-butyl peroxide (TBHP), and the free radical reductant is sodium bisulphite formaldehyde (SFS).

[0012] The redox system of the present invention can provide free radicals, and at the same time, under the action of low-temperature synthetic small materials, the reaction activation energy of the polymerization system is greatly reduced, so that the polymerization reaction can be carried out at room temperature, initial free radical active species are generated and chain reactions are initiated, which has the advantages of low energy consumption and high rate.

[0013] The second object of the present invention is to provide a method for preparing the above-mentioned underwater stabilizer for offshore wind power grouting material, comprising the following steps: S1. Fully mix the free radical reducing agent, molecular weight limiting agent, low temperature synthetic small material and 80-120 parts of deionized water to prepare material A for standby use; fully mix acrylamide, crosslinking agent and 120-150 parts of deionized water to prepare material B for standby use; S2, add self-made monomer sodium acrylate and 2-acrylamide-2-methylpropanesulfonic acid to a reactor into which nitrogen is passed, stir and fully dissolve, add free radical oxidant, then first add material A dropwise for 1.5-2.5h, then start to add material B dropwise for 1-2h; S3, after the addition of material A and material B is completed, stop passing nitrogen into the reactor, and transfer the synthesized product to a countercurrent rotating packed bed for high gravity synthesis, adjust the rotor speed to 700-850r / min, and react in a high gravity environment for 25-30min; S4. After the reaction is completed in the supergravity environment, 50-100 parts of deionized water are added to generate a diluted material, and then the diluted slurry is transported to a high-pressure homogenizer with the pressure controlled at 85-135 bar to obtain a colorless and transparent underwater stabilizer for offshore wind power grouting materials.

[0014] The present invention adopts aqueous solution polymerization, supergravity synthesis and high-pressure homogenization process to prepare a low molecular weight polyacrylamide offshore wind power grouting material underwater stabilizer, with a viscosity average molecular weight (Mv) of 1.2×10 5 -1.4×10 5 The molecular weight distribution is more uniform, the product performance is more stable, and the preparation process of the present invention is simple, the reaction conditions are mild, and it is all carried out at room temperature, the production cost is low, and it is conducive to large-scale production.

[0015] The beneficial effects of the present invention are: The invention uses sodium acrylate, acrylamide and 2-acrylamido-2-methylpropanesulfonic acid as main polymerization monomers, an added redox system provides free radicals, and a molecular weight limiter and a cross-linking agent control the molecular weight; multiple materials are coordinated, aqueous solution polymerization is adopted, and ultra-gravity synthesis and high-pressure homogenization processes are used to prepare an underwater stabilizer for offshore wind power grouting materials with uniform molecular weight distribution, stable product performance and good compatibility with a polycarboxylic acid water reducer, which can effectively improve the stability and water retention of the cement-based cementitious material system, enhance the stability of underwater construction of offshore wind power grouting materials, reduce strength loss, and improve overall stability and durability; solves the technical problems of bleeding, segregation, scouring and the like that are prone to occur in the current offshore wind power grouting materials, improves the rheological properties of the offshore wind power grouting material slurry, weakens the ion corrosion effect of the marine environment, and provides a guarantee for the normal application of various types of newly mixed offshore wind power grouting materials; and the invention has a simple preparation process and low production cost, which is conducive to large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 This is a picture of the underwater stabilizer for offshore wind power grouting prepared in Example 1 of the present invention; Figure 2 This is an infrared spectrum of an underwater stabilizer for offshore wind power grouting material prepared in Example 1 of the present invention; Figure 3 This is a diagram of the aggregation morphology of the underwater stabilizer of the offshore wind power grouting material prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0017] The instruments, reagents, materials, etc. involved in the following embodiments, unless otherwise specified, are all conventional instruments, reagents, materials, etc. in the prior art and can be obtained through regular commercial channels. The experimental methods, detection methods, etc. involved in the following embodiments, unless otherwise specified, are all conventional experimental methods, detection methods, etc. in the prior art.

[0018] Preparation of homemade monomer sodium acrylate: (a) adding 30 parts by weight of deionized water and 1.1 parts of acrylic acid to a reaction kettle, and starting stirring; (b) Sodium hydroxide was added to the reaction kettle to adjust the pH value of the solution to 7, and nitrogen was immediately introduced into the reaction kettle. The reaction was stirred at room temperature for 20 minutes to allow sufficient reaction to generate the self-made monomer sodium acrylate.

[0019] Cross-linking agent: N,N-methylenebisacrylamide; Molecular weight limiting agent: sodium methyl methacrylate sulfonate (SMAS); Free radical oxidant: tert-butyl peroxide (TBHP); Free radical reducing agent: sodium formaldehyde sulfoxylate (SFS); The low-temperature synthetic small material is alkali metal phosphate sodium phosphate; The above substances are used in the preparation of underwater stabilizers for offshore wind power grouting materials in the following examples or comparative examples.

[0020] Embodiment 1: An underwater stabilizer for offshore wind power grouting material, comprising the following components in parts by weight: 3.1 parts of homemade monomer sodium acrylate; 10 parts of acrylamide; 10 parts of 2-acrylamide-2-methylpropanesulfonic acid; 0.060 parts of cross-linking agent; 0.40 parts of molecular weight limiter; 2.0 parts of free radical oxidant; 1.0 parts of free radical reducing agent; 300 parts of deionized water; 0.2 parts of low-temperature synthetic small material; The method for preparing the underwater stabilizer for offshore wind power grouting material comprises the following steps: S1. Fully mix the free radical reducing agent, molecular weight limiting agent, low temperature synthetic small material and 100 parts of deionized water to prepare material A for standby use; fully mix acrylamide, crosslinking agent and 130 parts of deionized water to prepare material B for standby use; S2. Add self-made monomers sodium acrylate and 2-acrylamide-2-methylpropanesulfonic acid to a reactor filled with nitrogen and stir to fully dissolve, then add a free radical oxidant, start a constant flow peristaltic pump, start dripping material A, dripping for 2 hours, and then drip material B, dripping for 1.5 hours; S3, after the addition of material A and material B is completed, stop passing nitrogen into the reactor, and further transfer the synthesized product to a countercurrent rotating packed bed for high gravity synthesis, adjust the rotor speed to 750r / min, and react for 30min in a high gravity environment; S4. After the reaction is completed under the hypergravity environment, 70 parts of deionized water are added to generate a diluted material, and then the diluted slurry is transported to a high-pressure homogenizer, the pressure is controlled at 100 bar, and the homogenization is performed for 5 minutes. After the diluted slurry slowly passes through the valve port, a colorless and transparent underwater stabilizer for offshore wind power grouting material is obtained. Figure 1 .

[0021] The infrared spectrum of the underwater stabilizer for offshore wind power grouting prepared in Example 1 of the present invention is shown in Figure 2The infrared spectrum shows that the molecular structure contains characteristic functional groups such as carboxylic acid, amide and sulfonic acid, indicating that the polymer is obtained by copolymerization of three monomers: sodium acrylate, acrylamide and 2-acrylamide-2-methylpropanesulfonic acid. -1 -1610 cm -1 There is no characteristic absorption peak of C=C in the range, indicating that the free radical polymerization reaction has been fully carried out.

[0022] The aggregation morphology of the underwater stabilizer of the offshore wind power grouting material prepared in the embodiment of the present invention is shown in FIG. Figure 3 The aggregation form of polymer molecules in aqueous solution is mostly a spatial cross-linked network structure. The molecular chains are relatively long, and the molecular chains are entangled and agglomerated to form a cross-linked network structure. In addition to relying on the effect of hydrophilic groups in polymer molecules, this structure can also combine potential difference and osmotic pressure to prevent free water from migrating outward, thereby enhancing the underwater stability of wind power grouting materials.

[0023] Embodiment 2: An underwater stabilizer for offshore wind power grouting material, comprising the following components in parts by weight: 3.8 parts of homemade monomer sodium acrylate; 10.5 parts of acrylamide; 10.5 parts of 2-acrylamide-2-methylpropanesulfonic acid; 0.065 parts of crosslinking agent; 0.45 parts of molecular weight limiter; 2.5 parts of free radical oxidant; 1.2 parts of free radical reducing agent; 320 parts of deionized water; 0.3 parts of low-temperature synthetic small material; The method for preparing the underwater stabilizer for offshore wind power grouting material comprises the following steps: S1. Fully mix the free radical reducing agent, molecular weight limiting agent, low temperature synthetic small material and 120 parts of deionized water to prepare material A for standby use; fully mix acrylamide, crosslinking agent and 150 parts of deionized water to prepare material B for standby use; S2. Add self-made monomers sodium acrylate and 2-acrylamide-2-methylpropanesulfonic acid to a reactor filled with nitrogen and stir to fully dissolve, then add a free radical oxidant, start a constant flow peristaltic pump, and start dripping material A for 2 hours, and then drip material B for 1.5 hours; S3, after the addition of material A and material B is completed, stop passing nitrogen into the reactor, and further transfer the synthesized product to a countercurrent rotating packed bed for high gravity synthesis, adjust the rotor speed to 850r / min, and react for 30min in a high gravity environment; S4. After the reaction is completed in the high-gravity environment, 50 parts of deionized water are added to generate a diluted material, and then the diluted slurry is transported to the high-pressure homogenizer. The pressure is controlled at 100 bar and homogenized for 7 minutes. After the diluted slurry slowly passes through the valve port, a colorless and transparent underwater stabilizer for offshore wind power grouting material is obtained.

[0024] Comparative Example 1: An underwater stabilizer for offshore wind power grouting material, comprising the following components in parts by weight: 3.1 parts of acrylic acid monomer; 10 parts of acrylamide; 10 parts of 2-acrylamide-2-methylpropanesulfonic acid; 0.060 parts of crosslinking agent; 0.40 parts of molecular weight limiter; 2.0 parts of free radical oxidant; 1.0 parts of free radical reducing agent; 300 parts of deionized water; 0.2 parts of low-temperature synthetic small material; The preparation method of the underwater stabilizer for offshore wind power grouting material is the same as that in Example 1 and will not be repeated here.

[0025] Comparative Example 2: An underwater stabilizer for offshore wind power grouting material, comprising the following components in parts by weight: 3.1 parts of homemade monomer sodium acrylate; 10 parts of itaconic acid; 10 parts of 2-acrylamide-2-methylpropanesulfonic acid; 0.060 parts of crosslinking agent; 0.40 parts of molecular weight limiter; 2.0 parts of free radical oxidant; 1.0 parts of free radical reducing agent; 300 parts of deionized water; 0.2 parts of low-temperature synthetic small material; The preparation method of the underwater stabilizer for offshore wind power grouting material is the same as that in Example 1 and will not be repeated here.

[0026] Comparative Example 3: An underwater stabilizer for offshore wind power grouting material, comprising the following components in parts by weight: 3.1 parts of homemade monomer sodium acrylate; 10 parts of acrylamide; 10 parts of maleic acid; 0.060 parts of crosslinking agent; 0.40 parts of molecular weight limiting agent; 2.0 parts of free radical oxidant; 1.0 parts of free radical reducing agent; 300 parts of deionized water; 0.2 parts of low-temperature synthetic small material; The preparation method of the underwater stabilizer for offshore wind power grouting material is the same as that in Example 1 and will not be repeated here.

[0027] Comparative Example 4: An underwater stabilizer for offshore wind power grouting material, comprising the following components in parts by weight: 3.1 parts of homemade monomer sodium acrylate; 10 parts of acrylamide; 10 parts of 2-acrylamide-2-methylpropanesulfonic acid; 0.060 parts of cross-linking agent; 0.40 parts of molecular weight limiter; 2.0 parts of free radical oxidant; 1.0 parts of free radical reducing agent; 300 parts of deionized water; 0 parts of low-temperature synthetic small material; The preparation method of the underwater stabilizer for offshore wind power grouting material is the same as that in Example 1 and will not be repeated here.

[0028] Comparative Example 5: An underwater stabilizer for offshore wind power grouting material, comprising the following components in parts by weight: 3.1 parts of homemade monomer sodium acrylate; 10 parts of acrylamide; 10 parts of 2-acrylamide-2-methylpropanesulfonic acid; 0 parts of cross-linking agent; 0.40 parts of molecular weight limiting agent; 2.0 parts of free radical oxidant; 1.0 parts of free radical reducing agent; 300 parts of deionized water; 0.2 parts of low-temperature synthetic small material; The preparation method of the underwater stabilizer for offshore wind power grouting material is the same as that in Example 1 and will not be repeated here.

[0029] Comparative Example 6: An underwater stabilizer for offshore wind power grouting material, comprising the following components in parts by weight: 3.1 parts of homemade monomer sodium acrylate; 10 parts of acrylamide; 10 parts of 2-acrylamide-2-methylpropanesulfonic acid; 0.060 parts of crosslinking agent; 0 parts of molecular weight limiter; 2.0 parts of free radical oxidant; 1.0 parts of free radical reducing agent; 300 parts of deionized water; 0.2 parts of low-temperature synthetic small material; The preparation method of the underwater stabilizer for offshore wind power grouting material is the same as that in Example 1 and will not be repeated here.

[0030] Comparative Example 7: Commercially available underwater stabilizer, UWB-2 from Haiyan Admixture Company.

[0031] Application or performance testing method: The underwater stabilizer for offshore wind power grouting prepared in the embodiment or comparative example is mixed with water, and then the wind power grouting slurry is prepared according to the proportions in Table 1. The fluidity and vertical expansion rate are tested with reference to JG / T408-2019 "Sleeve Grouting for Steel Bar Connection", and the strength is tested according to GB / T 37990-2019 "Technical Requirements for Underwater Non-dispersible Concrete Flocculants". The specific test results are shown in Table 2.

[0032] Table 1 Basic formula of wind power foundation grouting material

[0033] Table 2 Comparison of wind power foundation grouting material test results

[0034] From the test results of the comparative examples and comparative examples in Table 2, it can be found that the mechanical properties and working performance of the embodiments are better than those of the comparative examples, and have a significant improvement effect. Comparative Examples 1-3 use acrylic acid, itaconic acid, and maleic acid to replace sodium acrylate, acrylamide, and 2-acrylamide-2-methylpropanesulfonic acid small monomers, respectively, and the fluidity and underwater strength are significantly reduced, and the waterway strength ratio is reduced by 10%-20% compared with the embodiment. Comparative Examples 4-6 remove low-temperature synthetic small materials, cross-linking agents, and molecular weight limiting agents, respectively, compared with Comparative Examples 1-3, the fluidity does not change much, but the waterway strength ratio is further reduced, and the waterway strength ratio is reduced by 20%-44% compared with the embodiment. Comparative Example 7 uses a commercially available underwater stabilizer, which has a relatively small effect on the underwater strength, but the fluidity is significantly deteriorated, and the commercially available underwater stabilizer does not have a water-reducing effect, and the stability of the offshore wind power grouting material is poor.

[0035] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. An underwater stabilizer for offshore wind power grouting material, characterized in that: The composition comprises the following components in parts by weight: 3.1-3.8 parts of homemade monomer sodium acrylate; 10.0-10.5 parts of acrylamide; 10.0-10.5 parts of 2-acrylamide-2-methylpropanesulfonic acid; 0.060-0.065 parts of crosslinking agent; 0.40-0.45 parts of molecular weight limiter; 2.0-2.5 parts of free radical oxidant; 1.0-1.2 parts of free radical reducing agent; 250-370 parts of deionized water; 0.2-0.3 parts of low-temperature synthetic small material; The self-made monomer sodium acrylate is prepared by neutralizing acrylic acid with sodium hydroxide; The low-temperature synthetic small material is alkali metal phosphate; the molecular weight limiting agent is sodium methyl methacrylate sulfonate.

2. The underwater stabilizer for offshore wind power grouting material according to claim 1, characterized in that: The method for preparing the self-made monomer sodium acrylate comprises the following steps: (a) adding 30-50 parts by weight of deionized water and 1.0-1.5 parts by weight of acrylic acid to a reaction kettle, and starting stirring; (b) Sodium hydroxide was added to the reaction kettle to adjust the pH value of the solution to 7-8, and nitrogen was immediately introduced into the reaction kettle to react for 15-25 minutes to generate the homemade monomer sodium acrylate.

3. The underwater stabilizer for offshore wind power grouting material according to claim 1, characterized in that: The crosslinking agent is one or more of N,N-methylenebisacrylamide, carbodiimide, and 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane crosslinking agent.

4. The underwater stabilizer for offshore wind power grouting material according to claim 1, characterized in that: The free radical oxidant and the free radical reductant constitute a redox system, and the redox system is a tert-butyl peroxide-sodium bisulfite formaldehyde system, a diacyl peroxide-cyclopentaneate system or a dialkyl peroxide-thiol system.

5. The underwater stabilizer for offshore wind power grouting material according to claim 4, characterized in that: The tert-butyl peroxide-sodium bisulphite formaldehyde system consists of a tert-butyl peroxide free radical oxidant and a sodium bisulphite formaldehyde free radical reductant.

6. A process for preparing an underwater stabilizer for offshore wind power grouting material according to any one of claims 1 to 5, characterized in that: The steps include: S1. Fully mix the free radical reducing agent, molecular weight limiting agent, low temperature synthetic small material and 80-120 parts of deionized water to prepare material A for standby use; fully mix acrylamide, crosslinking agent and 120-150 parts of deionized water to prepare material B for standby use; S2, add self-made monomer sodium acrylate and 2-acrylamide-2-methylpropanesulfonic acid to a reactor into which nitrogen is passed, stir and fully dissolve, add free radical oxidant, then first add material A dropwise for 1.5-2.5h, then start to add material B dropwise for 1-2h; S3, after the addition of material A and material B is completed, stop passing nitrogen into the reactor, and transfer the synthesized product to a countercurrent rotating packed bed for high gravity synthesis, adjust the rotor speed to 700-850r / min, and react in a high gravity environment for 25-30min; S4. After the reaction is completed in the supergravity environment, 50-100 parts of deionized water are added to generate a diluted material, and then the diluted slurry is transported to a high-pressure homogenizer with the pressure controlled at 85-135 bar to obtain a colorless and transparent underwater stabilizer for offshore wind power grouting materials.

Citation Information

Patent Citations

  • Method for quickly preparing anionic polyacrylamide

    CN104193896A

  • Acrylate aqueous solution grouting material and preparation method thereof

    CN108299599A

  • Grout composition

    JP1998324551A